2013
DOI: 10.1007/s10930-013-9490-5
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Spectroscopic Characterization and o-Diphenoloxidase Activity of Hemocyanin from a Freshwater Gastropod: Pila globosa

Abstract: Hemocyanins are multi-subunit oxygen carrier proteins, found in select species of arthropoda and mollusca. Here, we have purified native hemocyanin from Pila globosa, a freshwater gastropod, verified using mass spectrometry and determined its molecular weight, secondary structure and the spectral properties, using Ultraviolet/visible, Fourier transform infra-red and Circular dichroism spectroscopy. Our results reveal the oligomeric and glycosylated nature of the protein, comprising of 400 kDa subunits, organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Prior studies have reported different versions of tyrosinase-based biosensors for detection of phenols in environmental samples [33][34][35][36]. Two recent reports, one from our group [7] and the other by Raynova et al [5] described hemocyanin-based optical biosensors built by immobilizing molluscan hemocyanin on a thin film of chitosan coated on a glass slide. This first-generation sensor was able to detect catechol at concentrations of 5 ppm to 90 ppm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have reported different versions of tyrosinase-based biosensors for detection of phenols in environmental samples [33][34][35][36]. Two recent reports, one from our group [7] and the other by Raynova et al [5] described hemocyanin-based optical biosensors built by immobilizing molluscan hemocyanin on a thin film of chitosan coated on a glass slide. This first-generation sensor was able to detect catechol at concentrations of 5 ppm to 90 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…However, it suffers from lower affinity for bulky phenolic substrates. Currently, optimal phenoloxidase activity in hemocyanins is obtained by either carrying out limited proteolysis [5] or pretreatment with SDS [7], prior to its immobilization on sensors. Thus, it is important to understand the structural changes caused by the action of proteolytic agents or SDS resulting in an increase in the affinity of the protein for bulky phenolic substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e unhatched eggs were broken and the state of embryonic development [7] was observed to determine the rate of early embryonic mortality (number of eggs with a dead embryo without a shell) and late embryonic mortality (number of eggs having a dead embryo with shell). At the end of the experiment, each animal of each treatment was sacrificed; the hemolymph was removed by cardiac puncture according to the method proposed by [8] to determine the total protein and cholesterol. Shell, soft tissue, pedals mass, total meat, and gonads were collected for evaluation of carcass characteristics and relative weight [9].…”
Section: Conduct Of the Experiments And Data Collectionmentioning
confidence: 99%
“…Hemocyanin is a multimeric, type-3 copper containing, oxygen carrier protein that exhibits phenoloxidase-like activity and is found in select species of arthropoda and mollusca. The phenoloxidase activity in molluscan hemocyanin can be stimulated either by the proteolytic removal of its C-terminal β-rich sandwich domain (Campello et al, 2008) or by denaturation with SDS (Naresh, Krupanidhi, & Rajan, 2013), both of which enhance active site access to phenolic substrates (Coates & Nairn, 2014). The mechanism of SDS-induced activation is however not well studied.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%